2022
DOI: 10.56189/jagris.v2i1.27547
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PENGGUNAAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN TANAMAN KACANG HIJAU (Vigna radiata L.) PADA TANAH PESISIR

Abstract: This study aims to determine the effect of using goat manure on plant growth and to determine the best dose on the growth of mung bean (Vigna radiata L.) on the coastal land of Nambo. The study was conducted from June to August 2021. The study used a Randomized Block Design (RBD) which consisted of 7 treatments and 3 replications so that 21 experimental units were obtained, namely (K0) control 0 g polybags, (K1) 50 g polybags are equivalent to 10 tons ha, (K2)100 g polybags are equivalent to 20 tonsha, (K3)150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…(Marviana & Utami, 2014). Several research results on green bean plants using goat manure showed significant growth results (Kurniawati et al, 2022), optimal production (Risnah et al, 2022) and total fruit increase (Afif et al, 2014). Other research has been done use Liquid organic fertilizer also shows significant on chilli production (Warsito, 2022) .Purpose of this research is for know influence giving dung goats combined with liquid fertilizer from plant nails.…”
Section: Introductionmentioning
confidence: 94%
“…(Marviana & Utami, 2014). Several research results on green bean plants using goat manure showed significant growth results (Kurniawati et al, 2022), optimal production (Risnah et al, 2022) and total fruit increase (Afif et al, 2014). Other research has been done use Liquid organic fertilizer also shows significant on chilli production (Warsito, 2022) .Purpose of this research is for know influence giving dung goats combined with liquid fertilizer from plant nails.…”
Section: Introductionmentioning
confidence: 94%